Comparative genomic analysis of Helicobacter pylori isolates from gastric cancer and gastritis in China - Peng-fei Kong; Yong-hao Yan; Yan-tao Duan; Yan-tian Fang; Yi Dou; Yong-hu Xu; Da-zhi Xu (BMC Cancer)
Abstract Background This study aimed to explore and compare the genomic characteristics and pathogenicity of Helicobacter pylori (H. pylori) strains derived from the gastric cancer (GC) and gastritis in the Chinese population. Methods We performed whole genome sequencing on 12 H. pylori strains obtained from GC and gastritis patients in China. Additionally, we retrieved sequencing data for 20 H. pylori strains from various regions worldwide from public databases to serve as reference genomes. An evolutionary tree was constructed based on comparative genomics, and we analyzed the differences in virulence factors (VFs) and gene functions. Results In the GC strains, we identified 1,544 to 1,640 coding genes, with a total length ranging from 1,549,790 to 1,605,249 bp. In the gastritis strains, we found 1,552 to 1,668 coding genes, with a total length spanning from 1,552,426 to 1,665,981 bp. The average length of coding genes was approximately 1,594 (90.91%) for GC strains and 1,589 (90.81%) for gastritis strains. We observed a high degree of consistency in the VFs predicted for both cohorts; however, there was a significant difference in their cagA status. Clustering analysis showed significant core single nucleotide polymorphisms (SNPs) differences between GC and gastritis strains, but no major differences in homologous proteins or gene islands. Subsequent pan-genomic and Average Nucleotide Identity (ANI) analyses indicated high homology among GC, gastritis, and other reference H. pylori strains. Furthermore, gene function annotation results showed substantial similarity in gene functions between the H. pylori strains from GC and gastritis patients, with specific functions primarily concentrated in metabolic processes, transcription, and DNA repair. Conclusions H. pylori strains derived from GC and gastritis patients exhibit differences in virulence factors and SNPs, yet they demonstrate high genomic homology across other levels in the Chinese population.